1993
DOI: 10.1073/pnas.90.8.3246
|View full text |Cite
|
Sign up to set email alerts
|

Direction of handedness linked to hereditary asymmetry of a sensory system.

Abstract: Studies on the role of heredity in the transmission of handedness in nonhuman mammals have, so far, led to the isolation of mouse strains that differed in the lateralized versus ambidextrous use of the forepaw in a food-retrieval task (strength of paw preference). Here we report that left versus right use of the forepaw (direction of paw preference) is associated with a genetically expressed structural asymmetry of a sensory system, the whisker-to-barrel pathway. Mice that express whisker pad asymmetry of a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…When a cortical functional area, for example the somatosensory area, is enlarged in only one hemisphere, it can lead to lateralized sensorimotor control such as paw preference in mice (Barneoud and Van der Loos, 1993). Our previous work showed that LMO4 cortical region-specific expression is asymmetric between the two hemispheres in humans (Sun et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…When a cortical functional area, for example the somatosensory area, is enlarged in only one hemisphere, it can lead to lateralized sensorimotor control such as paw preference in mice (Barneoud and Van der Loos, 1993). Our previous work showed that LMO4 cortical region-specific expression is asymmetric between the two hemispheres in humans (Sun et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Deflection of the right whiskers evokes a spatially extended positive BOLD response in the contralateral somatosensory cortex (Alonso Bde et al, 2008). Thus, larger HMPAO uptake in the left than in the right somatosensory cortex might be associated with predominantly "right-whiskeredness" of the included mice, which in turn might be associated with left-handedness (Barneoud and Van der Loos, 1993). However, we did not examine our mice for paw preference.…”
Section: Lateral Asymmetrymentioning
confidence: 95%
“…Functional lateralization could also be a result of space constraint in the brain. In mouse, the bias in front-paw use is inversely correlated with the side of the face displaying supernumerary whiskers, and this has been suggested to result from competition for cortical space between the size of motor and somato-sensory areas (10).…”
Section: Advantage Of Functional Lateralization Of the Brainmentioning
confidence: 99%